Potential Role of Dissolved Oxygen and Manganese Concentration on the Development of Biofilms Causing Reduction in Hydraulic Capacity of a Gravity-Fed Irrigation System - Carstens, Alno; Bryant, Lee D.; Botes, Marelize; Wolfaardt, Gideon M. (Frontiers in Water, 2020)
Water from the Blyderiver dam in the Mpumalanga province, South Africa (SA), is used for gravity-fed irrigation. Biofilm development in the irrigation pipelines causes an increase in pipeline surface roughness leading to reduction of hydraulic capacity, resulting in water delivery below design capacity for the production of a variety of produce. The potential role of manganese (Mn) concentration on biofilm development is of interest, since the water is currently extracted at depth near the bottom of the reservoir (approximately 45-50 m when at 100% capacity) where high Mn levels were measured during four sampling events spread over two years. In the water body, dissolved oxygen (DO) and Mn concentrations showed a strong, inverse correlation, with rapid decrease in DO at increased depth, mirrored by an increase in both total and soluble Mn. The depth of this inflection point was found to correlate with the reservoir’s water level. DO concentrations typically remained constant between 8 and 9 mg l-1 in the upper regions of the water column, followed by a rapid decline to lower than 2 mg l-1 at deeper depths. Similarly, Mn concentrations remained constant with increasing depth, ranging between 10 and 100 µg l-1, followed by a rapid increase once the depth is reached where DO levels started to decline, up to 8631 µg l-1 near the bottom. In the main, 1.5 m diameter pipeline, Mn concentrations decreased with distance; from 8631 µg l-1 at the extraction point to 134 µg l-1 at 23 km downstream in the bulk aqueous phase, while in the biofilm biomass, Mn concentrations decreased from 30105.4 mg kg-1 at 4.5 km to 23501.9 mg kg-1 at 12.5 km, and 13727.7 mg kg-1 at 28.4 km downstream. This decrease in Mn concentration with distance suggests that biofilm accumulation has not yet reached a steady state.